Collaborative role of E2F transcriptional activity and G(1) cyclindependent kinase activity in the induction of S phase - Leone, Gustavo (The National Academy of Sciences, 1999)
A considerable body of evidence points to a role for both cyclin E/cyclin-dependent kinase (cdk)2 activity and E2F transcription activity in the induction of S phase. We show that overexpression of cyclin E/cdk2 in quiescent cells induces S phase, that this coincides with an induction of E2F activity, and that coexpression of E2F enhances the cyclin E/cdk2-mediated induction of S phase. Likewise, E2F overexpression can induce S phase and does so in the apparent absence of cyclin E/cdk2 activity. In addition, although the inhibition of cyclin E/cdk2 activity blocks the induction of S phase after growth stimulation of normal mouse embryo fibroblasts, inhibition of cyclin E/cdk2 does not block S phase induction in Rb−/− cells where E2F activity is deregulated. These results point to the important roles for E2F and cyclin E/cdk2 in the induction of S phase. Moreover, the nature of the E2F targets and the suspected targets for cyclin E/cdk2 suggests a potential molecular mechanism for the collaborative action of cyclin E/cdk2 and E2F in the induction of S phase.